Tingkat Kepedulian Orangtua Terhadap Pemberian Susu Pada Masa Pertumbuhan Anak Usia Sekolah - Niken Hartanti; Salsabila Aprilia; Chiquita Ashlaha Nuha; Vika Fathiara Afifah; Risma Rahmatunisa; Fensca Maria Rupidara (Jurnal Gizi dan Kuliner, 2022)
AbstractMilk is a source of protein that has high quality because of its complete nutritional content suchas protein around 3.5% with fat content around 3.0-3.8%. Milk is also a good source ofphosphorus and is very rich in calcium. However, the level of milk consumption in Indonesiais still relatively low. According to the Central Statistics Agency (BPS), milk consumption inIndonesia is only 12.1 L/capita per year. Thus, milk consumption in Indonesia, especially inschool-age children, needs special attention. This study aims to determine the level of parentalconcern for giving milk to school-age children. This study used a descriptive-analytical methoddesign by using a questionnaire. The results showed that giving milk to school children wasrecommended to consume milk in one day. Therefore, it can be concluded that parents careabout giving milk to school-age children.Keywords : level of concern, Growth Period, Milk